PERAMALAN PERGERAKAN INFLASI DI JAWA TIMUR DENGAN MENGGUNAKAN METODE TRIPLE EXPONENTIAL SMOOTHING - Alvin Nuralif Ramadanti; Elok Indana Zulfa; Noviati Maharani Sunariadi; Dian C. Rini Novitasari (Jurnal Matematika Sains dan Teknologi, 2021)
The economic growth of a nation is strongly influenced by inflation. Inflation is the continuous soaring price of goods or services. This study aims to predict the movement of inflation that will occur in East Java from January 2021 to December 2021. This study uses 48 data from the East Java Province inflation rate data from January 2017 to December 2020 sourced from the official website of BPS East Java. Predictions using the triple exponential smoothing method with forecasting evaluation using MAPE. Based on the analysis results, the parameters used are âº = 0,01, Î² = 0,09 dan Î³ = 0,30 which produces a MAPE value of 1.619%, which is classified as very good. The results show that the inflation forecasting from January 2021 to December 2021 is estimated at -0.13 to 0.48, with an average of 0.087. Thus, the movement of inflation in East Java from January 2021 to December 2021 is classified as low inflation, so it shows that prices and services are still stable.